PENGUATAN PENDIDIKAN KARAKTER GUNA MEMPERBAIKI POLA KARAKTER PESERTA DIDIK DI KELAS III MADRASAH IBTIDAIYAH - AISYAH NIHAYATUL FAUZIYAH HUMAM; ELSA SULISTIYA; ALVIN YANUAR RAHMAN (Universitas Trilogi, 2022)
The purpose of this study is to determine efforts to strengthen Character Education in elementary schools, using the character education pattern applied in Ibtidaiyah Madrasah. This research uses a qualitative type of descriptive research with a case study design. In this study, for data collection using observation techniques, and interviews. The results of this study concluded that: 1) Strengthening character education in students at the MI level is the responsibility of schools and parents, 2) The value of educational character patterns is applied and shown in MI Matala'ul Atfal with good habituation, such as dhuha prayer, muroja'ah, zuhr prayer in school and others. 3) strategies used by teachers in the application of Character education can be by example, routine activities that are applied every day When learning, application of religious values, responsibility, honesty, tolerance, and so on. 4) Obstacles obtained in efforts to strengthen character education, namely due to an environment that does not support the process of strengthening character education, factors of teachers who do not absorb good habituation, parents who do not teach character education at home, as well as the factors of the students themselves